Protocol for Care After Lymphoma (CALy) trial: a phase II pilot randomised controlled trial of a lymphoma nurse-led model of survivorship care - Taylor, Karen (BMJ Open, 2016)
INTRODUCTION: Lymphoma is the sixth most common cancer diagnosed in Australia and internationally. Owing to the aggressive nature of the disease and intensity of treatment, survivors face long-term effects that impact on quality of life. Current models of follow-up post-treatment fail to address these complex issues. Given that 74% of patients with lymphoma cancer now survive 5 years beyond diagnosis and treatment, it is important to address this gap in care. AIM: To determine self-reported informational and practical needs, anxiety, depression, stress, coping and empowerment at baseline, 3 and 6 months. METHODS AND ANALYSIS: A pilot randomised controlled trial will test the effect of a nurse-led lymphoma survivorship clinic compared with usual post-treatment care at a large tertiary cancer centre in Western Australia. The intervention will comprise three face-to-face appointments with delivery of tailored resources, a survivorship care plan and treatment summary (SCP TS). The SCP TS will be given to the participant and general practitioner (GP). Intervention participants will be interviewed at completion to explore the perceived value of the intervention components and preferred dose. An evaluation developed for GPs will assess receipt and use of SCP TS. The primary intent of analysis will be to address the feasibility of a larger trial and requisite effect and sample size. ETHICS AND DISSEMINATION: Ethics approval has been granted by the University of Notre Dame Australia and Sir Charles Gairdner Hospital in Western Australia. Peer-reviewed publications and conference presentations will report the results of this phase II trial. TRIAL REGISTRATION NUMBER: ANZCTRN12615000530527; Pre-results.